Mitochondrial D-Loop Analysis Reveals High Haplotype Diversity in the Belitung Tarsier (Cephalopachus bancanus saltator) - Dea Ardinaya; Wahid Herlanda; Muharni; Laila Hanum; Arum Setiawan; Indra Yustian (HAYATI Journal of Biosciences, 2026)
Habitat fragmentation from ongoing land clearing on Belitung Island poses a critical threat to Cephalopachus bancanus saltator, an endangered primate species endemic to the region. Comprehensive genetic data for this subspecies remain scarce, and this study aimed to assess its genetic diversity by analyzing mitochondrial Displacement Loop (D-loop) sequence variation. Ear tissue samples from six individuals were collected at two geographically distinct sites, Bukit Peramun and Batu Mentas. DNA extraction, amplification using DLTARPROF and DLTARBFR primers, and sequencing produced fragments ranging from 418 to 424 base pairs. Comparative BLAST analysis revealed sequence similarity of 88.12% to 89.76% with Tarsius bancanus (GenBank accession NC_002811.1). Haplotype diversity (Hd) reached 1.0 in both populations, indicating exceptionally high intraspecific variation. Pairwise genetic distances ranged from 0.0074 to 0.0370, while divergence from the outgroup species Carlito syrichta reached 0.1777. Phylogenetic reconstruction using the neighbor-joining method identified two distinct clades, with bootstrap support values ranging from 68% to 93%. The results indicate high haplotype diversity among the sampled individuals, likely attributable to the small sample size (n = 6) and the use of D-loop markers. These findings are preliminary and provide a baseline for future genetic studies. Safeguarding forest connectivity and reducing habitat loss are essential to preserve this high level of genetic diversity, which is critical for maintaining the long-term survival, adaptability, and evolutionary potential of this vulnerable primate.